Penerapan Teknik Equivalence Partitions pada Pengujian Aplikasi Seleksi Kenaikan Jabatan di PT Maju Makmur - Ahmad Nasrullah; Bukhari Muslim; Christian Harta Wijaya; Deni Pirmantara; Aries Saifudin (Program Studi Teknik Informatika Universitas Pamulang, 2020)
The accuracy of the output of the employee selection application for promotion is very important, because if something goes wrong it can harm the company. Employees who are selected and misplaced can cause lower performance of the employee concerned or other employees. To ensure that the resulting promotion application has met the requirements and is free from defects / errors, testing is necessary. In this study, it is proposed to do black box testing using the Equivalence Partition technique. Black Box testing is carried out based on the resulting input and output values regardless of the process or algorithm in the application. Meanwhile, the Equvalence Partition technique is done by dividing the input value domains into valid and invalid groups, then selecting and using one of the values from each of these groups. Testing the promotion selection application is carried out on 4 forms, namely the Add Criteria form, Edit Criteria, Add Alternatives, and Edit Alternatives. In this test, 8 test cases were made. The results of this test ensure the quality of the Promotion Promotion application is free from errors by finding an accidental error in the Promotion Promotion Selection application at PT Maju Makmur.